Validation of finite-element model of clamp of rail fastening system - V. O. Berezin; A. V. Zamukhovsky; A. A. Efimov; A. V. Grechanik (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. This paper discusses the validation and verif ication process of the finite element model (FEM) of the elastic clamp of the rail fastening system. Validation and verif ication are conducted to obtain clamp model that allows to sufficiently evaluate the stress-strain state of clamp condition for specified loading cases. Reliable calculation results signif icantly reduce the possibility of mismatch of stiffness and strength indicators with design characteristics. Materials and methods. The elastic clamp CP369.102 is chosen as the clamp under study. The development of its FEM is carried out considering real geometry of the product obtained by 3D scanning and the elastic-plastic model of the material. The verification of the FEM is conducted by analysing the mesh convergence, the quality of finite elements and by comparing with the results of analytical calculation. Validation involves comparison of natural and virtual experiment results for two parameters: the stiffness of the clamp in the pressure zone on the end sections and the stresses on the lateral sections of the clamp. The strain gauge method was chosen as the method for measuring stresses is the natural experiment.Results. The obtained results showed acceptable convergence between the natural and virtual experiments for two parameters: the stiffness of the clamp in the pressure zone on the end sections and the stresses on the lateral sections of the clamp. For the f irst parameter, the deviation between natural and virtual experiments is 4 %, for the second — from 8.3 to 15.4 %. These indicators testify to the suff icient accuracy of the developed model.Discussion and conclusion. Possible reasons for the discrepancy of the results for the stress parameter are proposed and discussed. Further studies are planned to improve the accuracy of the developed FEM, aimed at evaluating the sensitivity of strain gauges to transverse and tangential deformations. Validation of the FEM conf irmed its suitability for use in engineering calculations for clamp design, development of clamp test methods based on it, and other scientific research.